Proliferative glomerulonephritis with monoclonal immunoglobulin G3 lambda deposits accompanied by glomerular positive staining for nephritis-associated plasmin receptor and related plasmin activity: A report of two cases - Uchida, Takahiro; Oda, Takashi; Hoshino, Takahiko; Sakai, Takashi; Kojima, Aki; Inoue, Dan; Kojima, Tadasu; Yamada, Muneharu (Frontiers in Medicine, 2023)
Proliferative glomerulonephritis with monoclonal immunoglobulin (Ig) G deposits (PGNMID) is a relatively uncommon entity of monoclonal gammopathy of renal significance, and its detailed pathogenesis is not well understood. We, herein, report two cases of patients with PGNMID; their renal biopsy showed glomerular histological features of membranoproliferative glomerulonephritis pattern with endocapillary proliferation accompanied by non-organized granular electron-dense deposits that consisted of monoclonal IgG3-lambda. Neither symptomatic episodes of preceding infection nor infection foci were found in both patients; however, glomerular positive staining for nephritis-associated plasmin receptor (NAPlr) and related plasmin activity were observed. Although NAPlr was originally considered as a candidate nephritogenic protein for poststreptococcal acute glomerulonephritis, its positive staining and related plasmin activity have been observed in glomeruli of various cases with bacterial infection-related glomerulonephritis and is considered to be a general histological biomarker of infection-related glomerulonephritis. The present cases suggest that evaluation of immunoreactivity for NAPlr and related plasmin activity in glomeruli provides an important clue regarding the infection-related pathogenesis of PGNMID.